Desigualdades educacionais, fracasso escolar e questão racial - Freitas, Gabriel Rocha (2023)
This research, of a bibliographic and documentary nature, aims to comprehend the school failure in its relationship with the racial issue in articles published in the journal Cadernos de Pesquisa, in the period between 2018 and 2022 and in the analysis of the document Trajetórias do Sucesso Escolar published by Unicef based on data from the Brazilian School Census. It adopts dialectical-historical materialism as a theoretical reference, highlighting the contributions of Florestan Fernandes and Octavio Ianni to the discussion about racial issue in Brazil and the studies of Maria Helena Souza Patto to investigate the school failure instance. The selected material was examined using an analysis and documentation spreadsheet based on the guidelines for reading and analyzing academic texts (Gil, 2002; Lima and Mioto, 2007; Severino, 2016). The analysis of the selected studies of the journal Cadernos de Pesquisa indicates the emphasis on anti-racist education as the main action to confront racism in school, articulated with two main points: the concern with the implementation of educational policies centered on critical racial approach curricula and the defense of educational practices with such approach, particularly in relation to teaching performance. Within the context of this documental analysis, it was possible to identify an emphasis on school success supposedly justified by the improvement of statistical indices related to grade retention, dropping out, and age-grade distortion. However, it is observed that such displacement obscures historical contradictions intrinsic to racism, which is an essential point to be deepened in further studies. The findings also point out that the Brazilian public school in the scope of Basic Education is more challenging for Black students, especially for male children.